2013
DOI: 10.1016/j.foreco.2013.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Root functioning, tree water use and hydraulic redistribution in Quercus suber trees: A modeling approach based on root sap flow

Abstract: Mediterranean evergreen oaks have to survive a long summer drought. Roots may play a relevant role under these conditions. We studied their structure and function in a mature Quercus suber L. tree in central Portugal. The root system was mapped till the lowest water table level (4.5 m depth). Xylem anatomy was analyzed in a vertical profile belowground. Sap flow was continuously monitored for 1.5 yrs in the stem and roots of this intensively studied tree (heat field deformation method) and in the stem of four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
122
0
10

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 159 publications
(143 citation statements)
references
References 35 publications
(55 reference statements)
11
122
0
10
Order By: Relevance
“…This strategy is particularly important for evergreen trees that must survive a dry season. Several studies confirmed that Mediterranean oaks (Quercus suber and Quercus ilex in the Iberian Peninsula and Quercus douglasii in California) use this deep rooting strategy to tap water from groundwater reservoirs, whenever the superficial soil is dry and the water table is within the reach of the deep roots (David et al, 2004(David et al, , 2007(David et al, , 2013Lubczynski & Gurwin, 2005;Miller et al, 2010;Barbeta et al, 2015). This drought avoidance trait has also been observed in Australia (Zencich et al, 2002;O'Grady et al, 2006), South Africa (Le Maitre et al, 1999), China (Yin et al, 2015) and even in temperate forests during occasional droughts (Dolman, 1988).…”
Section: Leaf Sheddingmentioning
confidence: 80%
See 2 more Smart Citations
“…This strategy is particularly important for evergreen trees that must survive a dry season. Several studies confirmed that Mediterranean oaks (Quercus suber and Quercus ilex in the Iberian Peninsula and Quercus douglasii in California) use this deep rooting strategy to tap water from groundwater reservoirs, whenever the superficial soil is dry and the water table is within the reach of the deep roots (David et al, 2004(David et al, , 2007(David et al, , 2013Lubczynski & Gurwin, 2005;Miller et al, 2010;Barbeta et al, 2015). This drought avoidance trait has also been observed in Australia (Zencich et al, 2002;O'Grady et al, 2006), South Africa (Le Maitre et al, 1999), China (Yin et al, 2015) and even in temperate forests during occasional droughts (Dolman, 1988).…”
Section: Leaf Sheddingmentioning
confidence: 80%
“…This is particularly relevant in evergreen oaks in dehesas and montados, where a low density tree stratum coexists with pasture or crops in the open spaces. Ploughing, which has a damaging effect on tree root systems (superficial roots are connected to sinkers, see Figure 4), should be avoided as well as soil compaction promoted by heavy machinery or livestock overpressure (Hillel, 1982;Nadezhdina et al, 2012;David et al, 2013). Ploughing activities and livestock browsing have also been found to affect negatively cork oak natural regeneration (Pausas et al, 2009;Arosa et al, 2015), and may contribute to the spread of diseases and modify the physical properties of soils (Bugalho et al, 2009).…”
Section: Adaptation Measures For Managing Forests Under Enhanced Droughtmentioning
confidence: 99%
See 1 more Smart Citation
“…40) depends on the water potential gradients. Changes in the direction of flow therefore depend on the local soil water supply, which can differ significantly in soil layers at different depths , 2012b, David et al 2013 or if water storage is highly asymmetrical around the tree ). Deep soil layers can supply water to shallow soil layers via tap or sinker roots under drought if they contain more water.…”
Section: Open Field-applicable Methods For Whole Trees and Standsmentioning
confidence: 99%
“…Hasil penelitian sebelumnya di tingkat lapangan dan skala pot ditemukan adanya fenomena hydraulic lift (HL) pada tanaman jambu mete, karena setiap terjadi kehilangan lengas tanah di lapisan atas akibat proses evapotranspirasi yang tinggi pada siang hari selalu diikuti oleh proses pemulihan peningkatan lengas tanah pada periode setelahnya (Pitono et al 2016a;Pitono et al 2016b). Fenomena tersebut melengkapi temuan-temuan sebelumnya yang menyatakan bahwa lebih dari 30 spesies tanaman hutan dan gurun telah teridentifikasi memiliki kemampuan HL (Caldwell et al 1998;Bleby et al 2010;Prieto et al 2011;David et al 2013;Rocha et al 2014;Evaristo et al 2015).…”
Section: Pendahuluanunclassified